Characteristics And Anaerobic Digestion Of Fruits Wastes From Ubungo-Urafiki Market In Dar Es Salaam - Richard, Edwin N.; Mayo., Aloyce, W.; Kimwaga., Richard, J. (Tanzania Journal of Engineering and Technology, 2018)
Fruits are susceptible to mechanical damages during their transfer to the markets if they are not packed well in containers. Hence fruits wastes are generated in large quantities and because of their organic nature they decompose, which leads to environmental problems. The objective of this research was to quantify and characterize the fruits wastes generated from the Ubungo Urafiki Market in Ubungo Municipality and to establish the potential treatment of these wastes by anaerobic digestion. The data were collected in the field to establish the characteristics quantity of wastes generated in order to determine the potential degradation of fruit wastes using anaerobic digestion process. The market receives seven main kinds of fruits including pineapples, mangoes, water melons, avocados, oranges; paw paws and ripe bananas, which generate about 4.85 tons of fruit wastes per day. The leading fruits with higher percentage of wastes were water melons and oranges, which generated about 800 kg/day and 797 kg/day, respectively. The results of batch plants experiments showed that the reactor with fruit waste-cattle manure-wood ash mixtures had a maximum biogas yield of 34.2 liters while the reactor with fruit wastes-mixtures had lowest biogas yields of 0.1 liters. The reactor with fruit waste- wood ash mixtures had high volatile solid and total solid removal efficiencies of 8.0% and 14.3%, respectively. For the maximization of biogas production wood ash was recommended in order to raise the pH value of the fruit wastes. The batch reactor used in this study was limiting pH control and therefore activities of methanogenic bacteria. It is recommended to adopt a semi continuous or continuous reactor in order to limit excessive production of organic acids, which are responsible for inhibition of biogas production. Key words: Anaerobic digestion, Biogas, Fruit Wastes.